Study of Antimicrobial and Antibiofilm Effect of Essential Oils on Biofilm Producing Staphylococcus aureus Isolated from Mastitis Milk of Bovines - Mishra, Durgesh; Shrivastava, Arpita; Shrivastava, Neeraj; Ranjan, Rajeev; Kiran Niranjan, Ankush (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present work was undertaken to study antimicrobial and antibiofilm effect of essential oils on the biofilm producing Staphylococcus aureus isolated from the bovine mastitis milk. Out of 164 dairy cattle and buffalo milk samples screened, 24 samples were found positive for mastitis by CMT. Among these, 17 S. aureus isolates were identified and characterized phenotypically by standard biochemical tests. The biofilm formation ability of the isolates was studied by Congo red agar, Light microscopy method and Microtiter plate (Crystal Violet) method. The antimicrobial activity and antibiofilm effect of essential oils - Garlic and Cinnamon oil - on biofilm positive S. aureus were studied by agar well diffusion method and Microtiter plate method, respectively. Cefoperazone was used as standard control drug. Out of the total 17 S. aureus strains,70% were positive on Congo red agar, 52% by Light microscopy and 100% on Microtiter plate method. By the Microtiter plate method, 4 strains were strong biofilm producers and 13 were weak biofilm producers. Cinnamon oil showed better antibiofilm activity in all the concentration used (1%, 2%, 3%). Garlic oil showed good antimicrobial and antibiofilm activity at 3% concentration.It was concluded that biofilm producing Staphylococcus aureus was isolated from bovine mastitis milk samples, and sensitivity of Congo red agar, Light microscopy and Microtiter plate methods was good. Micro titre plate showed highest sensitivity for detection of biofilm production. Garlic oil and Cinnamon oil showed antimicrobial and antibiofilm producing abilityagainst S. aureus.